Sustainability of SMEs on environmental compliance in leather industry in developing countries - Singh, Shweta; S., Rajamani (2007)
Environmental laws define the scarcity of environmental resources they affect the factor endowment of a country and therefore its position in the international division of labour. There is now also a general agreement that applying the ‘polluter pays’ principle should solve environmental problems. As the burden of abatement increases, as measured by the ratio of abatement expenditure to sales, there is definitely an incentive for firms to either invest in cleaner technology or more efficient abetment technology. There is also evidence that taxes and charges, designed to internalize externalities can actually affect trade. It is interesting to know if the developing countries face particular market access problems in the face of stringent environmental standards and regulations. While its true that stringent measures impose market access restrictions and cause limitations on competitiveness, this is much widely felt by the developing countries because of lack of infrastructure and monitoring facilities, limited technology choices, inadequate access to environment – friendly raw materials, lack of complete information, presence of small-scale exporters and emergence of environmental standards in sectors of export interest to developing countries. The small and medium enterprises often divert sales either to the domestic market to external markets where environmental requirements are less stringent, in order to save on their costs. Whereas 80% of the industry is reserved for small and medium enterprises (SMEs) in the tanning sector from raw to semi-finished leather mostly processing less than 2 tons per day. In Europe and other developed countries the SMEs in leather sector have vanished due to strict environmental compliance and this will likely occur in developing countries also. The environmental compliance too has not always been practical, either because the laws are too ambitious or unrealistic in certain parameters, or because they have lacked effective instrumentation and institutional support. Some environmental regulations have not succeeded as they do not match the technical requirements and economic reality of the country or region, or because they do not take the institutional capabilities of the society that has to implement them into consideration. Where as 80% of the industry is reserved for SMEs in the tanning sector from raw to semi-finished leather mostly processing less than 1 to 2 tons per day. For the survival and sustenance of the SMEs in the leather industry, it may be a viable alternative to carry out the tanning process in a decentralized fashion such that the raw to semi-finish process is carried out in the large scale sector while the semi-finished to finished process could either be reserved or open to competition as per the countries’ requirements. But the issue of concern is whether it is fair that the raw to semi-finished tanning process, containing 70% pollution discharge should be undertaken by developing countries alone, especially if it is at the cost of their survival! However, the game analyzed in the paper reveals that tanning units in developing countries would prefer to comply with the regulations and stay in the industry, the alternatives being to collude or to compete!